EVALUASI FAKTOR IMPLEMENTASI KEBIJAKAN PELAYANAN ADMINISTRASI TERPADU KECAMATAN (PATEN) DI KECAMATAN TAMANSARI KABUPATEN BOYOLALI - Tiyas Nur Haryani; Bagas Suryo Prihantoro (P3M STISIPOL Dharma Wacana Metro, 2022)
Boyolali Regency in 2018 carried out the division of sub-districts, namely the expansion of Musuk District which resulted in new sub-districts, one of which was Tamansari District. One of the factors causing the sub-district expansion policy is the large number of villages in the expanded sub-district area. Therefore, the purpose of this expansion is to bring public services closer to the village community. This study aims to examine the evaluation of PATEN implementation factors in Tamansari District as a new sub-district by using an analysis seen from the basic policy of the Minister of Home Affairs Regulation Number 4 of 2010 concerning Guidelines for Integrated District Administration Services and Boyolali Regent Regulation Number 34 of 2015 concerning Delegation of Part of the Regent's Authority to Camat in the Framework of Implementing Integrated District Services within the Boyolali Regency Government (substantive requirements, administrative requirements and technical requirements) and the theory of policy implementation factors belonging to Van Meter and Van Horn which researchers elaborated with Edward III (communication, resources, bureaucratic structure, standards and targets). policies, disposition of implementers, and indicators of social, economic, political conditions). Collecting data by interview, documentation, and observation. The results of the research on the implementation of PATEN are based on the policy basis, namely the substantive requirements, administrative requirements and technical requirements that have not been fully met even though some are not optimal. Administrative requirements for the type of company registration service (TDP) and industrial business licenses (SIUI) are not available, and technical requirements still have not been fulfilled, namely the place of payment and cash holder officers because in Tamansari District all services are free of charge. While the results of the analysis according to Van Meter and Van Horn with Edward III show that the supporting factors are the communication indicators; resource; bureaucratic structure; standards and goals; executor disposition; and social, economic and political conditions, but still found obstacles in these factors, communication; resource; standards and goals; and social, economic and political conditions.